Collaborative governance in tourism development in the city Surabaya after pandemic - Priambodo, Bayu (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2022)
The tourism sector in the pandemic era is the sector most affected. So far, the development of the tourism sector, especially in big cities, has only focused on government and private actors. In big cities, there are two groups of people: local communities and urban communities. This community group in the tourism development process was never involved. Surabaya is one of the second largest cities in Indonesia, where the development of the tourism sector is carried out quite massively. From this problem, the researcher wants to see how the collaborative governance process in the city of Surabaya is. This study used qualitative methods, and data search techniques were carried out through in-depth interviews. Data analysis in this study uses the collaborative governance theory of Ansell and Gash. The results show that collaborative governance in Surabaya has not been synchronized between fellow actors. It can be seen from the government actors who have two tourism promotion institutions, but these two institutions are still running independently. The community actors are also not involved in the tourism development process, which can be seen from the people who do not know when there is tourism development in the area where they live. Meanwhile, private actors who act as developers in the development process do not use local communities as workers. Post-pandemic collaborative governance in developing societies cannot run effectively because their resources are less than optimal.